2011
DOI: 10.1007/s10666-010-9248-9
|View full text |Cite
|
Sign up to set email alerts
|

Extended Analytical Turbulent Diffusion Model for Particle Dispersion and Deposition in a Horizontal Pipe: Comparison with CFD Simulation

Abstract: A 2D analytical turbulent diffusion model for particle dispersion and deposition at different heights along the pipe flow and circumferential deposition has been developed. This liquid-solid turbulent diffusion model presented in this paper has emanated from an existing gas-liquid turbulent diffusion model. This model can be used as a handy tool for quick estimation one and twodimensional deposition fluxes of particles in water distribution networks. A comprehensive 3D numerical investigation has been carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It can be shown that under modest turbulent flow regimes the behavior of a suspended particle as large as 44 μm (about 100 times the 0.45 μm threshold for particulate lead) will be dominated by turbulent diffusivity rather than inertia (Stk < 0.2). At such a low Stokes number, particles are expected to precisely follow the turbulent fluctuations of the flow stream, 37 can be modeled as a solute tracer. Therefore, the transport of mobilized particulate lead with the bulk flow is described by a 2-D convective-diffusion equation…”
Section: ■ Methodolgymentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that under modest turbulent flow regimes the behavior of a suspended particle as large as 44 μm (about 100 times the 0.45 μm threshold for particulate lead) will be dominated by turbulent diffusivity rather than inertia (Stk < 0.2). At such a low Stokes number, particles are expected to precisely follow the turbulent fluctuations of the flow stream, 37 can be modeled as a solute tracer. Therefore, the transport of mobilized particulate lead with the bulk flow is described by a 2-D convective-diffusion equation…”
Section: ■ Methodolgymentioning
confidence: 99%
“…It can be shown that under modest turbulent flow regimes the behavior of a suspended particle as large as 44 μm (about 100 times the 0.45 μm threshold for particulate lead) will be dominated by turbulent diffusivity rather than inertia (Stk < 0.2). At such a low Stokes number, particles are expected to precisely follow the turbulent fluctuations of the flow stream, and hence, their transport can be modeled as a solute tracer. Therefore, the transport of mobilized particulate lead with the bulk flow is described by a 2-D convective-diffusion equation where C p is the particulate lead concentration in the bulk flow (μg/L), D L,p and D r,p are the apparent diffusivities of particulate lead in the longitudinal and radial directions, respectively (cm 2 /s), and R set is the rate of particulate lead settling (μg/L/s).…”
Section: Methodolgymentioning
confidence: 99%
“…3D Navier-Stokes equations (Sohr 2012) were considered for the simulation of flow and heat transfer and energy equation for steady incompressible fluid with constant properties. The flow is described by the conservation laws for mass (continuity), momentum (Navier-Stokes) and by the energy equations are as follows (Hossain and Naser 2011, Bhuiyan and Naser 2014:…”
Section: Mathematical Modellingmentioning
confidence: 99%